TYPOLOGY OF THE COMPULSORY COMPONENT PROTOTYPES OF THE FIXED PHRASE SCHEMES AS SOURCES OF SYNTACTIC CONSTRUCTIONS GRAMMATICALIZATION (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-93-104The study relevance is due to the leading role of the compulsory component prototype of the fixed phrase scheme as a source of syntactic construction grammaticalization as a whole. The purpose of the work is to describe the prototypes typology of the compulsory component of the fixed phrase scheme, as well as to establish trends in their use, based on the methodology of the grammaticalization theory and the theory of idiomatization. It is proved that the idiomatization of syntactic constructions is determined by their grammaticalization. One of the leading sources of syntactic constructions grammaticalization is lexical-semantic means, the list of which is limited. They are represented by lexemes with a generalized meaning, that act as a compulsory component prototype of the fixed phrase scheme: syncategorematic words (more common), as well as full denominative words with primary grammaticalization (rare) and without primary grammaticalization (exception). The linguistic nature of particular prerequisites for the grammaticalization of syntactic constructions, which determines the launch of the grammaticalization process, is described. It is established that the main source of their grammaticalization is the “simplicity” (“generalization”) of lexical-semantic meaning. Additional sources are meanings of “interrogation” (seme “uncertainty”), and “motivation” (seme “unreality”), some circumstantial meanings of subordinate clauses (“condition”, “concession”, “assumed assumption”, “place”), which are characterized by the seme “unreality” as well as the meaning of “determinative” (seme “uncertainty”). The study prospect is the description of the grammaticalization index of source constructions, as well as the productivity of their grammaticalization prerequisites.Key words: sources of syntactic constructions grammaticalization, prototype of compulsory component of fixed phrase scheme, syncategorematic words, denominative words